the graph of y = x2 11x 24 is equivalent to the graph of which equation? a.y = (x 8)(x 3) b.y = (x 4)(x 6) c.y = (x 9)(x 2) d.y = (x 7)(x 4)

Answers

Answer 1
Answer:

Answer:

Option a is correct.

Step-by-step explanation:

We have been given the expression:

y=x^2+11x+24

We will factorize the given quadratic equation:

x^2+8x+3x+24

\Rightarrow x(x+8)+3(x+8)

\Rightarrow (x+8)(x+3)

Hence, the given equation is equivalent to (x+8)(x+3)

Hence, the graph will be equivalent to y=(x+8)(x+3)

Therefore, option a is correct.

Answer 2
Answer: y = x^2 + 11x + 24 = (x + 8)(x + 3)

Related Questions

What transformations change the graph of f(x) to the graph of g(x)? f(x) = 3x2 g(x) = 9x2 - 4
Which expressions are completely factored?Choose all answers that are correct. Question 4 options: 18x^4 – 12x^2 = 6x(3x^3 – 2x) 12x^5 + 8x^3 = 2x^3(6x^2 + 4) 20x^3 + 12x^2 = 4x^2(5x + 3) 24x^6 – 18x^5 = 6x^5(4x – 3)
2+1=I still cannot firnd the answer I am so silly plz someone teleel me in 1 min
True or False:8. V 40 has an infinite non-repeating decimal expansion.9. The number 0.56 is a rational number10. 200 and 500 are integers.11. All numbers with infinite decimal expansions are irrational.12.the numbers -8, -3, 5, 17 are all whole numbers.
Create a system of linear equations that has the coordinates (birth year, birth month) as its only solution. for example, november 2007 coordinates will be (7,11) they must both be diagonal, not horizontal or vertical. A) graph your system and clearly state your two linear equations. B) prove algebrically that your solution is (your birth year, your birth month) by subsituition or elimination. C) verify algebrically that your point (birth year, birth month) is the solution to your system of equations

If 3x^2-2x+7=0,then (x-1/3)^2= please help with detailed steps because i dont really understand it. I know the answer is -20/9 but please explain

Answers

Answer:

-(20)/(9)

Explanation:

A quadratic function is a kind of function with highest degree 2 .  Standard form of the quadratic equation : tex]ax^2+bx+c=0[/tex]

Further explanation:

Consider the given quadratic equation : 3x^2-2x+7=0  

First we divide both sides  by 3 , we get

x^2-(2)/(3)x+(7)/(3)=0--------(1)

Compare this equation to x^2+2ax+a^2 , we have

2a=(-2)/(3)  

\Rightarrow\ a=(-1)/(3)  [divide both sides by 2]

Now using the completing the squares method , Add and subtract ((-1)/(3))^2 to the left side in (1), we get

x^2-(2)/(3)x+((-1)/(3))^2-((-1)/(3))^2+(7)/(3)=0  

It can be written as

(x^2-2((1)/(3))x+(1)/(3))^2)-(1)/(9)+(7)/(3)=0  

Use identity x^2-2ax+a^2=(x-a)^2, we have

(x-(1)/(3))^2)+(7(3)-1)/(9)=0  

(x-(1)/(3))^2)+(20)/(9)=0  

Subtract (20)/(9) from both the sides , we get

(x-(1)/(3))^2)=-(20)/(9)

Therefore, the value of (x-(1)/(3))^2)=-(20)/(9)

Learn more :

Keywords :

Quadratic equation, standard form, completing squares method, Polynomial identities.

For this case we have the following polynomial:

3x^2-2x+7=0

To solve the problem, we must complete squares.

The first step is to divide the entire expression by 3.

We have then:

(3)/(3)x^2-(2)/(3)x+(7)/(3)=0

The second step is to place the constant term on the right side of the equation:

(3)/(3)x^2-(2)/(3)x=-(7)/(3)

The third step is to complete the square:

(3)/(3)x^2-(2)/(3)x + (-(1)/(3))^2=-(7)/(3)+ (-(1)/(3))^2

Rewriting we have:

x^2-(2)/(3)x + (1)/(9)=-(7)/(3)+ (1)/(9)

(x-(1)/(3))^2 = -(20)/(3)

Answer:

By completing squares we have:

(x-(1)/(3))^2 = -(20)/(3)

Need the answer
What are the values of​ x, y, and​ z?

Answers